2019
DOI: 10.1101/706176
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dopaminergic modulation of the exploration/exploitation trade-off in human decision-making

Abstract: Acknowledgements: This work was funded by Deutsche Forschungsgemeinschaft (grant PE1627/5-1 to J.P.). Large parts of this publication are based on the dissertation "Dopaminergic modulation of the explore/exploit trade-off in human decision making" by K.C. (Chakroun, Karima: Dopaminergic modulation of the explore/exploit trade-off in human decision making [online]; Hamburg, Univ., Diss., 2019; Summary A central issue in reinforcement learning and decision-making is whether to exploit knowledge of reward values,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 170 publications
1
9
0
Order By: Relevance
“…On the other hand, some PET studies in humans did not find a relation between EBR and DA synthesis capacity 31 or D2/3-receptor availability 30 . More recently, in a pharmacological study, Chakroun et al 58 found no modulation of the EBR by L-dopa (DA precursor) and haloperidol (D2 receptor antagonist).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, some PET studies in humans did not find a relation between EBR and DA synthesis capacity 31 or D2/3-receptor availability 30 . More recently, in a pharmacological study, Chakroun et al 58 found no modulation of the EBR by L-dopa (DA precursor) and haloperidol (D2 receptor antagonist).…”
Section: Discussionmentioning
confidence: 98%
“…After ovulation, the luteal phase is characterized by increasing levels of progesterone and medium estradiol levels 56 . However, some of the studies including the EBR as putative index for DA system only include males 5,29,57 , and others explicitly state that female sex hormones could affect their measurements 58 . This sex bias towards male subjects is even more pronounced in animal research ( 16,59 in monkeys 19 , in rodents).…”
mentioning
confidence: 99%
“…An intriguing candidate for this is dopamine, whose phasic responses have been shown to reflect state uncertainty (Starkweather et al, 2017;Babayan, Uchida, and Gershman, 2018;Lak et al, 2018), and whose tonic levels have been shown to modulate exploration in mice on a lever-press task (Beeler et al, 2010), and context-dependent song variability in songbirds (Leblois, Wendel, and Perkel, 2010). Dopaminergic genes have been shown to predict individual differences in uncertainty-guided exploration in humans (Frank et al, 2009), and dopaminergic disorders such as Parkinson's disease have been shown to disrupt the uncertainty-dependence of lapses across conditions on a multisensory task (Bertolini et al, 2015), while L-Dopa, a Parkinson's drug and dopamine precursor, has been shown to attentuate uncertainty-guided exploration (Chakroun et al, 2019). Patients with ADHD, another disorder associated with dopaminergic dysfunction, have been shown to display both increased perceptual variability and increased task-irrelevant motor output, a measure that correlates with lapses (Mihali et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important in the context of clinical groups that are known to show increased perseveration (van Timmeren et al, 2018). We addressed this issue by extending existing models of exploration with an additional perseveration bonus term, such that final estimates of directed exploration are unconfounded by potential group differences in perseveration (Chakroun et al, 2019). Indeed, the full model including both directed exploration and perseveration terms accounted for the data best in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, DA has been associated with reward prediction error coding and exploitation (Beeler, Daw, Frazier, & Zhuang, 2010;Pessiglione, Seymour, Flandin, Dolan, & Frith, 2006). But both theoretical accounts (Beeler, 2012) and empirical data (Chakroun, Mathar, Wiehler, Ganzer, & Peters, 2019;Cinotti et al, 2019;Frank, Doll, Oas-Terpstra, & Moreno, 2009;Gershman & Tzovaras, 2018;Kayser, Mitchell, Weinstein, & Frank, 2014) suggest a role of DA in regulating the explorationexploitation trade-off. DA also plays a role in problem gambling behavior.…”
Section: Introductionmentioning
confidence: 99%